AB0921 Infectious Spondylodiscitis Features: about 44 Cases. (15th July 2016) - Dhahri, R.; Gharsallah, I.; Boussetta, N.; Abid, R.; Metoui, L.; Laajili, F.
Abstract : Background: Spinal infections can be described aetiologically as pyogenic, granulomatous (tuberculous, brucellar, fungal) and parasitic. Its early diagnosis is crucial to the establishment of adequate treatment in order to get favorable outcomes. The aim of the present work was to describe clinical, diagnostic and therapeutic aspects of Infectious Spondylodiscitis according to the experience of an internal medicine department in Tunisia. Methods: Patients with SDI either confirmed or presumed and hospitalized in the internal medicine department of The Principle Military Hospital Of Tunis, Tunisia have been included in the Study. Results: Fourty-four patients met the inclusion criteria. They have been gathered over 20 years-period. They were 24 men and 20 women with an average age at 52.5 years. The diagnosis was a Tuberculous Spondylodiscitis in 22 cases (50%): among them 10 patients had a concomitant extra spinal TB. The diagnostic delay was 231 days for TB SDI and 40.5 days for SDP. Revealing symptoms were dominated by pain:, often mixed (61%). Radicular pain was noted in 15 cases. Fever was found in 17 cases. On examination: spinal syndrom was present in 65.9% of cases, spinal cord compression signs were found in 8 patients. MRI was contributive in all cases showing a disc enhancement in 50% (SDP in 67%, TSDI in 33%), epiduritis in 63.5% (SDP 60%, TSDI 67%). The disc biopsy was contributive in 71% of cases. The diagnosis was certain in 15 cases, highly probable in 18 cases and presumptive in 11 cases. Treatment duration was 13 months for SDT and 18 weeks for SDP. The outcome was favorable in 30 cases (SDP 13, TSDI 17). Conclusions: Infectious sondylodiscitis remains a diagnostic and therapeutic problem in our country. Only an early care can enhance its prognosis. Disclosure of Interest: None declared